Long-term didactic innovations in higher education teaching caused by the coronavirus pandemic? - Budke, Alexandra; Sanchez-Kirsch, Nichol; Quintero-Rivas, Erika (Frontiers in Education, 2023)
During the coronavirus pandemic, many universities worldwide were closed and lecturers had to switch from face-to-face teaching to online distance education. Consequently, questions arose which routines in teaching the lecturers were able to use despite this change in teaching environments, and which didactic innovations they implemented in their courses. Lecturers’ evaluation of these innovations and any aspects they intend to continue using after the pandemic and the return to face-to-face teaching were examined. Through a qualitative survey of 24 university lecturers in Germany and Panama, the long-term effects of the pandemic on teaching were investigated. It was found that the creation of new digital media for teaching, the use of new digital tools to ensure interaction and scientific exchange, the finding of new forms of organisation, and combinations of synchronous and asynchronous teaching were all considered to be positive didactic innovations that should be maintained after the pandemic.